2019
DOI: 10.1016/j.cattod.2018.11.064
|View full text |Cite
|
Sign up to set email alerts
|

Ni, Co, Fe supported on Ceria and Zr doped Ceria as oxygen carriers for chemical looping dry reforming of methane

Abstract: Chemical looping dry reforming of methane (CLDRM) consists in reacting CH4 with an oxygen carrier (OC) to produce syngas and subsequently oxidizing the OC using CO2. Based on previous work on Ni/CeO2, several ceria based OCs are explored. First, different preparation methods are compared. OCs obtained by Ni impregnation on homemade ceria or coprecipitation method show similar results while the use of a commercial ceria leads to an inactive carrier. Second, Zr doping of the carrier is shown to improve the therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 46 publications
0
54
0
Order By: Relevance
“…In total, the two compositions are designed such that the extent of exsolution is quite similar for both; this should allow us to deconvolute chemical from microstructural and nanostructural effects that cause any change in reactivity. 21,23,28 Upon oxidation, all of the metal phase is converted to the metal oxide phase, as indicated by X-ray diffraction and corresponding renement analysis. The increased peak broadening of the perovskite reveals a further increase in the microstrain inicted on the host matrix, by a factor of 5 as compared to the reduced state.…”
Section: Resultsmentioning
confidence: 99%
“…In total, the two compositions are designed such that the extent of exsolution is quite similar for both; this should allow us to deconvolute chemical from microstructural and nanostructural effects that cause any change in reactivity. 21,23,28 Upon oxidation, all of the metal phase is converted to the metal oxide phase, as indicated by X-ray diffraction and corresponding renement analysis. The increased peak broadening of the perovskite reveals a further increase in the microstrain inicted on the host matrix, by a factor of 5 as compared to the reduced state.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, 2Ni/CeO 2 and 38.5Ni/CeO 2 showed total oxidation and severe carbon deposition resulted from lack of sufficient Ni 0 for CH 4 activation and Ni 2+ species in Ce−Ni−O solid solution for oxygen supply, respectively. Then they further investigated the effect of preparation method, modification of CeO 2 (doping ZrO 2 ) and other active elements (Fe and Co) on the performance, and concluded that good balance of surface activity and bulk oxygen reactivity played a critical role for the increased conversion and selectivity at low temperature (600–650 °C) [71] . Unlike the work in terms of improving lattice oxygen diffusion above, the work undertook by Wang's research group remarkably enhanced lattice oxygen transport by a stoichiometric redox cycle promoted by catalytically active Ni [72] .…”
Section: Oxygen Carriersmentioning
confidence: 99%
“…Such flexibility is also beneficial to dry reforming reactions catalyzed by 3d transition metal catalyst (e. g., Ni), on which the carbon deposited can be cyclically removed in the CO 2 reactor, thereby eliminating the accumulation of coke. [191][192][193][194] This advantage is particularly relevant to feedstocks with strong coking tendencies such as bio-oil. [195] During CL-dry reforming, the catalysts are exposed to reacting gas mixtures that are different from conventional reformers.…”
Section: Chemical Loopingmentioning
confidence: 99%
“…For instance, during CL−CO 2 −ODH of alkanes, the coked catalyst could have a sufficiently long residence time in the CO 2 reactor (see Figure 10d) to ensure complete catalyst regeneration via the Boudouard reaction. Such flexibility is also beneficial to dry reforming reactions catalyzed by 3d transition metal catalyst (e. g., Ni), on which the carbon deposited can be cyclically removed in the CO 2 reactor, thereby eliminating the accumulation of coke [191–194] . This advantage is particularly relevant to feedstocks with strong coking tendencies such as bio‐oil [195] .…”
Section: Reaction Engineering Approachesmentioning
confidence: 99%